Epigenetic regulation of T‐helper cell differentiation, memory, and plasticity in allergic asthma. Issue 1 (July 2017) - Tumes, Damon J.; Papadopoulos, Magdalene; Endo, Yusuke; Onodera, Atsushi; Hirahara, Kiyoshi; Nakayama, Toshinori
Summary: An estimated 300 million people currently suffer from asthma, which causes approximately 250 000 deaths a year. Allergen‐specific T‐helper (Th) cells produce cytokines that induce many of the hallmark features of asthma including airways hyperreactivity, eosinophilic and neutrophilic inflammation, mucus hypersecretion, and airway remodeling. Cytokine‐producing Th subsets including Th1 (IFN‐γ), Th2 (IL‐4, IL‐5, IL‐13), Th9 (IL‐9), Th17 (IL‐17), Th22 (IL‐22), and T regulatory (IL‐10) cells have all been suggested to play a role in the development of asthma. Th differentiation involves genetic regulation of gene expression through the concerted action of cytokines, transcription factors, and epigenetic regulators. We describe how Th differentiation and plasticity is regulated by epigenetic histone and DNA modifications, with a focus on the regulation of histone methylation by members of the polycomb and trithorax complexes. In addition, we outline environmental influences that could influence epigenetic regulation of Th cells and discuss the potential to regulate Th plasticity and function through drugs targeting the epigenetic machinery. It is also becoming apparent that epigenetic regulation of allergen‐specific memory Th cells may be important in the development and persistence of chronic allergies. Finally, we describe how epigenetic modifiers regulate cytokine memory in Th cells and describe recently identified hybrid, plastic, and pathogenic memory Th subsets the context of allergic asthma.